Pronunciation competence and impact of phonetics and phonology instruction in the Vietnamese tertiary context - Nhat, Ton Nu My; Hien, Hoang Thi Thu (Penerbit Universiti Kebangsaan Malaysia, 2024)
A holistic approach to pronunciation instruction — encompassing both segmentals and suprasegmentals — is essential for enhancing the intelligibility and comprehensibility of second/foreign language learners. However, teachers often prioritise the accurate articulation of individual English consonants and vowels, neglecting the suprasegmental aspects of pronunciation. Therefore, a comprehensive examination of both segmental and suprasegmental aspects is imperative for evaluating the efficacy of pedagogical interventions and assessing the pronunciation proficiency of language learners. This study examines the pronunciation proficiency of Vietnamese EFL students at the tertiary level, an area with limited research. Additionally, it seeks to evaluate how theoretical knowledge of English phonetics and phonology influences their pronunciation performance. The quantitative data were obtained from a pre-and post-test involving 50 undergraduates majoring in English at a public university in Vietnam. The findings reveal that an overwhelming majority of the students displayed below-average pronunciation abilities. The study also documented the positive impact of participation in theoretical English phonetics and phonology on students. These findings have broader implications beyond the immediate context, offering valuable guidance to educators and learners in similar educational settings.